2020
DOI: 10.1111/cdev.13367
|View full text |Cite
|
Sign up to set email alerts
|

Youth’s Sibling Relationships Across the Course of a Parent’s Military Deployment: Trajectories and Implications

Abstract: The present exploratory study explored the trajectories and implications of at-home (military unaffiliated) parents' perceptions of youth's sibling relationships across the course of a parent's military deployment. Participants included 109 families with at least two siblings (older sibling and younger siblings age: M = 10.85, SD = 3.92 and M = 7.89, SD = 3.58, respectively) and one parent serving in the National Guard. Data were collected via in-home interviews, at six time points across the deployment cycle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, one study showed that the association between fathers’ perceived threat during a previous deployment and their preschool-aged children’s social–emotional adjustment was mediated not only by father-reported parent child interaction, but also by maternal reports of family-level emotional responsiveness (Hajal et al, 2020 ). A longitudinal study showed that school-aged children’s social–emotional adjustment over the course of a parents’ deployment was associated with sibling relationship quality, even beyond the impact of the non-deployed caregiver’s parenting practices (Whiteman et al, 2020 ).…”
Section: Expanding the Focus To Whole Family Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, one study showed that the association between fathers’ perceived threat during a previous deployment and their preschool-aged children’s social–emotional adjustment was mediated not only by father-reported parent child interaction, but also by maternal reports of family-level emotional responsiveness (Hajal et al, 2020 ). A longitudinal study showed that school-aged children’s social–emotional adjustment over the course of a parents’ deployment was associated with sibling relationship quality, even beyond the impact of the non-deployed caregiver’s parenting practices (Whiteman et al, 2020 ).…”
Section: Expanding the Focus To Whole Family Systemsmentioning
confidence: 99%
“…Sibling relationships have the potential to provide young children with some of their earliest experiences of intense positive (e.g., joy, excitement) and negative (e.g., frustration, anger, jealousy) emotions (Kramer, 2014 ; Lindsey, 2020 ). Furthermore, there is evidence that the quality of sibling relationships is a unique predictor of children’s psychosocial outcomes, beyond the contributions of caregiver–child relationships (McHale, Updegraff, et al, 2012 ; McHale, Waller, et al, 2012 ; Modry-Mandell et al, 2007 ; Stormshak et al, 2009 ; Whiteman et al, 2020 ). Sibling interactions may provide opportunities for children to observe their siblings model adaptive emotion regulation skills or to benefit from siblings who provide them with coregulation during moments of distress (Kramer, 2014 ).…”
Section: Expanding the Focus To Whole Family Systemsmentioning
confidence: 99%
See 2 more Smart Citations